مواجهة السعديين للغزو البرتغالي ( 917- 1511 986 - 1578 م) - بوكريمة أسماء (My University, 2025)
Summary: The subject of my research, titled "The Saadian Confrontation of the Portuguese Invasion (1511-1578 )," represents a rich historical field that sheds light on an important aspect of the political history of Morocco, namely the history of the Saadian state and the transformations it underwent during the modern period. . In this research, I addressed the Saadian confrontation of the Portuguese invasion following the inability of the Wattasid state to resist. The Saadian state relied on well-planned strategies led by strong sultans such as Mohammed al-Sheikh and Ahmad al-Mansur, which ended the Portuguese presence after victory in the Battle of Wadi al-Makhazin and reclaimed the major cities that had been under Portuguese control. These confrontations had positive impacts on the political, military, social, and cultural levels, especially during the period of Ahmad al-Mansur. -------------------------- الملخص بالعربية: إن موضوع البحث المعنون ب " مواجهة السعديين للغزو البرتغالي ( 917- 1511/ 986 - 1578 م) يمثل حقلا تاريخيا خصيبا يسمح بإنارة جانب مهم من التاريخ السياسي للمغرب الأقصى وهو تاريخ الدولة السعدية والتحولات التي جرت عليها خلال الفترة الحديثة. تطرقت في بحثي هذا إلى مواجهة السعديين للغزو البرتغالي بعد عجز الدولة الوطاسية عن المقاومة حيث إعتمدت الدولة السعدية على إستراتجيات محكمة بقيادة سلاطين أقوياء مثل محمد الشيخ وأحمد المنصور أنهت الوجود البرتغالي بعد إنتصار في معركة وادي المخازن و إسترجعت أهم المدن التي كانت تحت سيطرة البرتغال، و خلفت هذه المواجهات آثار إيجابية على الأصعدة السياسية و العسكرية و الأجتماعية و الثقافية خاصة خلال فترة أحمد المنصور. ---------------------- Résumé : Le sujet de ma recherche, intitulé « La confrontation des Saadiens à l’invasion portugaise ( 1511- 1578), représente un champ historique riche qui permet d’éclairer un aspect important de l’histoire politique du Maroc occidental, à savoir l’histoire de la dynastie saadienne et les transformations qu’elle a connues durant la période moderne. Dans cette étude, j’ai abordé la manière don’t les Saadiens ont fait face à l’invasion portugaise après l’incapacité de l’État wattasside à résister. L’État saadien s’est appuyé sur des stratégies rigoureuses sous la conduite de sultans puissants comme Mohammed al-Cheikh et Ahmed al-Mansour, ce qui a permis de mettre fin à la présence portugaise après la victoire à la bataille de Oued al-Makhazin et de reprendre les principales villes occupées par les Portugais. Ces confrontations ont eu des effets positifs aux niveaux politique, militaire, social et culturel, notamment durant le règne d’Ahmed al-Mansour.
Keywords: السعديين، الغزو البرتغالي ( 917- 1511/ 986 - 1578 م)